Treatment of Cutaneous Leishmaniasis in a Nonendemic Country: A Case Series of Children in Australia. Issue 4 (28th December 2021) - Hill, Nicholas; Irwin, Adam; Graham, Nicolette; Leung, Clare; Francis, Joshua R.; Wall, Nerilee; Nourse, Clare
Abstract : We describe 4 cases of cutaneous leishmaniasis in children in Australia. Treatment is challenging given lack of firm guidelines and limited access to conventional modalities used in endemic countries. Topical paromomycin or oral fluconazole were effective outpatient-based first-line treatments, however, topical paromomycin use was limited by expense to import or compound locally.